Cross-tissue transcriptome-wide association identify novel T1D susceptibility genes and drug candidates - Liu, Yiming; Cao, Yu; Jiang, Yaohui (Frontiers in Immunology, 2026)
BackgroundThe genetic mechanisms underlying type 1 diabetes (T1D) remain incompletely understood, limiting the development of targeted therapies.MethodsWe performed an integrative genetic analysis to identify T1D susceptibility genes and therapeutic targets. This included a cross-tissue transcriptome-wide association study (TWAS) to pinpoint genes with genetically predicted expression associated with T1D risk, followed by Mendelian randomization to infer causality. Identified genes were further characterized through pathway, cell-type enrichment, drug prediction, molecular docking, and phenome-wide association studies.ResultsWe identified ten genes associated with T1D risk, seven of which (ELK4, PHACTR4, MAST2, ST7L, C1orf216, SULT1A2, and WFS1) are novel candidates in this context. Three genes (ELK4, SULT1A2, and WFS1) were prioritized as druggable targets, with COMPOUND 5G and DCLK1-IN-1 emerging as potential therapeutic agents through computational analyses.ConclusionOur study reveals novel genetic associations and immune-related pathways in T1D pathogenesis, and proposes specific genes and compounds as promising focal points for future mechanistic and therapeutic exploration.